Development of flexible piezoresistive dielectric membrane by PVDF/Fe3O4. (2021) - Mohanty, Sribidhya; Panwar, Varij; Khanduri, Priya
Abstract: Polymer dielectrics with piezoresistive properties are being considered as a promising energy storage material, flexible wearable devices and smart devices. High dielectric property makes it efficient for its application in Thin Film Transistors (TFT) and battery separator and the piezoresistive property makes it efficient for flexible devices. In this paper, we present and analyse the dielectric, conductive and piezoresistive property of Polyvinylidene fluoride (PVDF)/Ferrous Ferric Oxide (Fe3 O4 ) in frequency band of 20 Hz to 10 MHz. Membrane showing high dielectric constant has been synthesized by blending PVDF and Fe3 O4 together. Initially the dielectric of pure PVDF membrane was low, but it increased with the addition of Fe3 O4 . The impedance analyser was used to measure dielectric constant, AC conductivity and dissipation factor. In this research paper we have concluded that on adding 1 gm of Fe3 O4 to PVDF, we have got the best result in terms of conductivity, dielectric constant and piezoresistive property. The conductivity of the membranes was strongly affected by Fe3 O4 content; conductivity increases with increase in Fe3 O4 content.